Determination of the effective dose of dexmedetomidine to achieve loss of consciousness during anesthesia induction - Mu, Bing; Xu, Wenjie; Li, Hongyi; Suo, Zizheng; Wang, Xiaoxiao; Zheng, Yuxiang; Tian, Yi; Zhang, Bowen; Yu, Jie; Tian, Naiyuan; Lin, Nan; Zhao, Dan; et al. (Frontiers in Medicine, 2023)
Background: Dexmedetomidine (DEX) is a sedative with greater preservation of cognitive function, reduced respiratory depression and improved patient rousability. This study was designed to investigate the performance of DEX during anesthesia induction, and to establish an effective DEX induction strategy, which could be valuable for multiple clinical condition. Methods: Patients undergoing abdominal surgery were involved in this dose-ﬁnding trial. Dixon up-and-down sequential method was employed to determine the effective dose of DEX to achieve the state ‘loss of consciousness’, and an effective induction strategy was established with continuous infusion of DEX and remifentanil. The effects of DEX on hemodynamics, respiratory state, EEG and anesthetic depth were monitored and analyzed. Results: Through the strategy mentioned, the depth of surgical anesthesia was successfully achieved by DEX-led anesthesia induction. The ED50 and ED95 of the initial infusion rate of DEX were 0.115 and 0.200 μg/kg/min, and the mean induction time was 18.3 min. The ED50 and ED95 of DEX to achieve the state ‘loss of consciousness’ were 2.899 (95%CI: 2.703-3.115) and 5.001 (95%CI: 4.544-5.700) μg/kg. The mean PSI on loss of consciousness was 42.8. among the patients. During anesthesia induction, the hemodynamics including BP and HR were stable, and EEG monitor showed decreased α and β power, and increased θ and δ in the frontal and pre-frontal cortices of brain. Conclusion: This study indicated that continuous infusion of combined DEX and remifentanil could be an effective strategy for anesthesia induction. The EEG during the induction was similar to physiological sleep process.